Umbilical cord fibroblasts: Could they be considered as mesenchymal stem cells? - Zeddou, Mustapha (Baishideng Publishing Group Inc, 2014)
In cell therapy protocols, many tissues were proposed as a source of mesenchymal stem cells (MSC) isolation. So far, bone marrow (BM) has been presented as the main source of MSC despite the invasive isolation procedure related to this source. During the last years, the umbilical cord (UC) matrix was cited in different studies as a reliable source from which long term ex vivo proliferating fibroblasts were isolated but with contradictory data about their immunophenotype, gene expression profile, and differentiation potential. Hence, an interesting question emerged: Are cells isolated from cord matrix (UC-MSC) different from other MSCs? In this review, we will summarize different studies that isolated and characterized UC-MSC. Considering BM-MSC as gold standard, we will discuss if UC-MSC fulfill different criteria that define MSC, and what remain to be done in this issue.